MECHANISM OF PERSONNEL MOTIVATION IN THE FORMATION OF INVESTMENT POLICY OF A FOOD INDUSTRY ENTERPRISE AND ENSURING ITS OPERATIONS - HAVLOVSKA, Nataliia; LUTIUK, Vasyl; RUDNICHENKO, Yevhenii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the features of food industry enterprises and highlights their typical specializations by stages of the technological cycle. The main principles of investment policy development are presented. It is determined that when solving multifunctional tasks, one of the main characteristics of the personnel who implements these tasks is intellectual potential. The intellectual capital of an employee consists of knowledge, skills, professional training, abilities, professional experience, acquired productive abilities that are inseparable from the employee and, to the extent that the employee wishes, are manifested in the labor process. It is proven that in the process of forming an investment policy, some employees may behave taking into account personal interests, which creates additional threats to the economic security of the enterprise. They may use their intellectual capital in such a way that creates threats to the security of the enterprise by abusing their official position, exceeding their official competences, or committing openly criminal offenses of an economic nature. That is why an effective motivation mechanism can eliminate such threats. The mechanism of motivation of the enterprise personnel in the general sense is a form of joint use of separate motivation tools, which in a certain combination are used to increase the interest of the enterprise employees in the effective solution of a specific task. The paper develops a mechanism of motivation of the personnel to form an investment policy and secure the activities of the enterprise. It is proved that the action of the mechanism of motivation of the personnel is aimed at forming such operant behavior of its employees, which involves not just the fulfillment of their functional duties or job instructions, but actions assigned to the employee by internal corporate documents or a contract, which ensure the relatively safe functioning of security facilities and the effective use of investment resources.